Relative Impact of Mindfulness, Self-Compassion, and Psychological Flexibility on Alcohol Use and Burnout Among Law Enforcement Officers - Kaplan, Josh (J Altern Complement Med, 2020)
Objectives: In the present study, we investigated the relative impact of improvements in mindfulness, self-compassion, and psychological flexibility in predicting decreased burnout and alcohol use in a sample of law enforcement officers (LEOs) participating in a mindfulness-based intervention (MBI). Design: This study is a secondary analysis of pre/post data collected as part of a larger randomized controlled trial of mindfulness-based resilience training (MBRT). Subjects: This secondary analysis comprises pre/post data from 28 LEOs recruited from a metropolitan area and its outlying regions in the Pacific Northwest. Intervention: MBRT is a MBI tailored specifically to the culture and needs of LEOs and other first responders. Outcome measures: All included data were obtained through self-report measures. Mindfulness was assessed by the Five Facet Mindfulness Questionnaire-Short Form, self-compassion was assessed by the Self-Compassion Scale-Short Form, psychological flexibility was assessed by the Acceptance and Action Questionnaire-II, alcohol use was measured by the PROMIS(®) (v1.0) Alcohol Use-Short Form, and burnout was assessed by the Oldenburg Burnout Inventory. Results: In the first regression, only increases in mindfulness significantly predicted decreased postintervention problematic alcohol use. In the second regression, only increases in self-compassion significantly predicted decreased postintervention burnout. Conclusions: This study builds upon a growing body of literature on the relative impact of mindfulness, self-compassion, and psychological flexibility in predicting outcomes among high-stress cohorts. Results suggest that different components of MBIs may be emphasized to achieve unique benefits. The Clinical Trial Registration number for the parent study is NCT02521454.